Validation of Сhoice of Laboratory Model for Preclinical Estimation of Medical Protectors Against Bolivian Hemorrhagic Fever - T. E. Sizikova; V. N. Lebedev; V. B. Pantukhov; E. Y. Vakhnov; S. V. Borisevich (Вестник войск РХБ защиты)
This review is dedicated to the peculiarities of pathogenesis of the experimental Bolivian hemorrhagic fever (BHF) - the disease, caused by Machupo virus (Arenaviridae family). The authors come to the conclusion that for carrying out preclinical researches of the medical means of protection (MMP) in vivo on small laboratory animals it is expedient to use guinea pigs, infected with a strain of Chicava or with a variant of Carvallo strain, adapted for these animals. The use of guinea pigs as small laboratory animals when studying pathogenesis of the disease caused by Machupo virus allows to carry out statistically reliable definition of quantitative indices of an experimental infection and to select medicines for the final stage of preclinical assessment. As arenaviruses block the process of formation of interferon (IFN) in the infected organism, mice, defective by IFN formation, are the perspective animal models for the study of BHF pathogenesis and may be used for the study of attenuated variants of Machupo virus. The Javanese macaques (Macaca fascicularis) are the laboratory animals, modeling the pathogenetic manifestations of BHF in humans. They can be used when carrying out the final stages of preclinical assessment of means of medical protection.